Archaeologies of Totalitarianism, Authoritarianism, and Repression : Dark Modernities - Symonds, James HerausgeberIn; Vařeka, Pavel 1967- HerausgeberIn (Palgrave Studies in Cultural Heritage and Conflict, 2020)
1. Introduction -- 2. Mass Graves: Strategies of Extermination during the Spanish Civil War and Franco´s Dictatorship -- 3. Concentration Camps: Classifying the Subjects of the New Spain -- 4. Double Vision and the Politics of Visibility: the Landscapes of Forced and Slave Labour -- 5. The Heart of Terror: A Forensic and Archaeological Assessment of the Old Gas Chambers at Treblinka -- 6. Materiality of a Forced Migration in WWII. Archaeology of Displacement of the Polish Exodus in Iran (From 1942) -- 7. Searching for Living Ghosts: The Archaeology of Communist Repression in Poland -- 8. Archaeology of the Lithuanian Partisan War: Case of the Partisan Bunker in Daugėliškiai Forest -- 9. Divided Landscapes, Divided Peoples: An Archaeology of the Iron Curtain between Czechoslovakia and Western Germany -- 10. The Shadow of Pain. Instructions for Archaeologists Living under Dictatorship.